Rhizosphere Microbial Community Structure Is Selected by Habitat but Not Plant Species in Two Tropical Seagrass Beds - Zhang, Xia; Zhao, Chunyu; Yu, Shuo; Jiang, Zhijian; Liu, Songlin; Wu, Yunchao; Huang, Xiaoping (Frontiers in Microbiology, 2020)
Rhizosphere bacterial community structures and their determining drivers have been studied in a variety of marine and freshwater ecosystems for a range of plant species. However, there is still limited information about the influence of habitat on microbial communities in seagrass beds. This study aimed to determine which factors (habitat and plant species) have crucial roles on the rhizospheric bacteria associated with two tropical seagrass species (Thalassia hemprichii and Enhalus acoroides) that are dominant at Xincun Bay and Tanmen Harbor in Hainan Island, South China. Using Illumina HiSeq sequencing, we observed substantial differences in the bacterial richness, diversity, and relative abundances of taxa between the two habitats, which were characterized differently in sediment type and nutrient status. Rhizospheric bacteria from sandy sediment at the eutrophic Xincun Bay was dominated by Desulfobacteraceae and Helicobacteraceae, which are primarily involved in sulfate cycling, whereas rhizosphere microbes from the reef flat at oligotrophic Tanmen Harbor was dominated by Vibrionaceae and Woeseiaceae, which may play important roles in nitrogen and carbon fixing. Additionally, we speculated that host-specific effects of these two seagrass species may be covered under nutrient rich conditions and in mixed community patches, emphasizing the importance of the nutrient status of the sediment and vegetation composition of the patches. In addition, our study confirmed that Proteobacteria was more adapted to the rhizosphere environment than to low carbon conditions that occurred in bulk sediment, which was primarily dominated by well-known fermentative bacteria in the phylum Firmicutes.